The Effectiveness of the Role of Sub-District Social Welfare Workers (TKSK) in the Poverty Prevention Program in the Social Office of Bone Bolango Regency - Lisdawati Muda; Zuchri Abdussamad; Sri Susanty Bata (Journal of Economic, Business, and Administration (JEBA), 2020)
Poverty is considered as a complex and multidimensional public problem. Poverty problems become a complex problem so that a country cannot have the ability to eradicate poverty on its own. The majority of Indonesians are at a low economic level. This condition causes the poverty rate in Indonesia to increase from year to year.In the context of accelerating poverty reduction as well as developing policies in the field of social protection, the Government of Indonesia has implemented various poverty alleviation programs such as the social assistance program. To make the program successful, it is assisted by a team of sub-district social welfare workers (TKSK). The purpose of this study was to determine and analyze the Role of Sub-District Social Welfare Workers (TKSK) in the Poverty Reduction Program at the Social Office of Bone Bolango Regency and its inhibiting factors.The analytical method used in this research was a qualitative data analysis method, using an interactive model. The data collection model used in this research was conducted through observation, interviews and documentation.Based on the results of the study, it shows that the role of sub-district social welfare workers (TKSK) in the Poverty Reduction Program considering from the aspect of the role as coordinator, role as facilitator and role as administrator has been implemented but has not been effectively implemented. It also considers the competency factors and hindering facilities.